Dimensional measurements on 112 GWd/t irradiated MOX fuel pins using X-ray radiography. (September 2015) - Saravanan, T.; Arunmuthu, K.; Lahiri, B.B.; Bagavathiappan, S.; Venkiteswaran, C.N.; Philip, John; Divakar, R.; Joseph, Jojo; Jayakumar, T.
Highlights: A modified X-ray radiography procedure is used to evaluate the fuel pellet integrity of 112 GWd/t irradiated MOX fuel pins. Dimensional measurements on MOX fuel pins showed 1.3% stack length increase after 112 GWd/t fuel burn-up. A 5 × 5 Laplacian kernel based edge detection algorithm was used for accurate measurement of fuel pin outer diameter. Abstract: The dimensional measurements such as fuel stack length, fuel pin diameter, pellet-to-pellet gap, plenum and spring length of 112 GWd/t irradiated Uranium Plutonium mixed oxide (MOX) fuel pins have been carried out using X-ray radiography. The X-ray radiography procedure is optimized for the exposure time, applied voltage, applied current to minimize the effect of high gamma radiations emitted from the irradiated fuel pins on the X-ray films. The dimensional measurements from the radiography images indicate a maximum increase in the stack length of 1.3%. The relatively low fuel swelling, compared to the carbide fuel, is attributed to the low fuel smear density and high fission gas release. The analyses of digitized radiography images revealed a few radial cracks in the fuel pellets. At the bottom portion of the fuel pins, pellet-to-pellet gaps and pellet-to-clad gaps are seen clearly. Our results indicate that after irradiation to 112 GWd/t, the spring length has compressed to ∼88.7 mm against the original value of 90 mm due to volumetric swelling of the fuel column. It is observed that the diametrical strain is highest at the central location of fuel pins and the spring column is compressed. The contrast sensitivity of the radiography images is enhanced by adopting image processing approaches. A 5 × 5 Laplacian kernel based edge detection technique is used to evaluate the fuel pin diameter accurately. The average increase in pin diameter, after irradiation, is found to be 50 μm.